Menstrual hygiene practices among Kom women in rural area of Chandel district, Manipur: a cross-sectional study - Serto, Ladiya; Rajkumari, Sumati (International Journal Of Community Medicine And Public Health, 2025)
Background: Menstruation is a normal physiological process and a key sign of reproductive health in women; it plays a vital role in women’s life. To acquire healthy reproductive menstrual hygiene is one significant aspect for women and this proper menstrual hygiene has not been fairly addressed in some rural tribal areas of Manipur. This study aimed to determine menstrual hygiene practices among Kom women in rural area of Chandel district, Manipur. Methods: A community based cross-sectional survey using pre-tested self-structure questionnaire, the questionnaire consisting of socio-demographic profile, menstrual history and menstrual hygiene practices. 300 eligible participants’ adult women were selected using purposive sampling method the study area was carried out among five kom villages residing in Chandel district of Manipur. Result: The mean age of study population was 34.63±8.76 years. Majority of them belonged to aged group 40-49 years (36.7%) and 64.7% were married. Used of sanitary pad during menstruation was reported by 71% and reusable cloths 29%. 16.3% of females reported irregular menstruation state and in times of irregular menstruation 92% of them mentioned they don’t seek medical treatment. Conclusions: Hence, menstrual history and practices were found to be unsatisfactory among the rural Kom women. Further studies with more qualitative study are recommended to take a look in rural tribal areas of Manipur. Health education classes and intervention session on reproductive health and menstrual hygiene practices among rural tribal community must be encourage to overcome the challenges faced by the rural tribal women.